Enhancing Hand Interactions and Accessibility in Virtual Reality Environments for Users With Motor Disabilities: A Practical Case Study on VR-Shopping - Ruben Grande; Javier Albusac; Vanesa Herrera; Dorothy Monekosso; Ana De Los Reyes-Guzman; David Vallejo; J. J. Castro-Schez (IEEE Access)
Over the past decade, Virtual Reality (VR) has achieved significant advancements in both quality and accessibility of its devices, particularly with VR headsets that offer an enhanced immersive experience at a reduced cost. This improvement is not only in graphical fidelity but also in interactivity within virtual environments, highlighted by advancements in tracking systems that allow direct manipulation with hands-free of external devices. However, these technologies are not fully adapted for use by individuals with motor disabilities in their arms and hands. This study addresses the ethical and moral obligation to make VR accessible to all users by proposing specific adaptations to the manual interaction mechanisms. Focusing on VR e-commerce as a use case, which is anticipated to revolutionize the shopping experience in the coming years, this study explores a scenario where users need to navigate and manipulate virtual products to examine and make purchase decisions. The experimental phase was conducted in a real-world setting at the Hospital Nacional de Parapléjicos in Toledo (HNPT), involving patients with spinal cord injuries and motor limitations. The results demonstrate that the adapted interactions not only enable users to perform tasks that are impossible with conventional mechanisms but also reduce the time and effort required to complete these tasks. Specifically, completion times achieved by users increased up to 91.6%. Also, the number of tasks completed highly increased in comparison with unadapted interactions. We elaborate an Effort Degree (ED) formula with various data items based on hand movements, that demonstrated that adapted interactions